Field performance comparison of the combine harvesters utilized for rice harvesting in Malaysia - Wagiman, N. A.; Nawi, N. M.; Yahya, A.; Su, A. S. M.; Nasir, R. M. (Rynnye Lyan Resources, 2019)
A large combine harvester has long been used for harvesting rice in Malaysia. Recently, a mini combine harvester has been introduced into this industry to be a low-cost alternative for a large combine harvester. Thus, this study was carried out to compare the field efficiency (FE), effective field capacity (EFC), fuel consumption (FC), and field machine index (FMI) between a mini combine harvester (MCH) and large combine harvester (LCH) under similar field conditions. The field performances of the combine harvesters were measured during harvest operation in two consecutive seasons. The EFC for both MCH and LCH in harvest operation were found to be 0.91 and 1.30 ha/hr, respectively. In terms of the FE, MCH had 0.78% higher efficiency than LCH. For the FMI, LCH and MCH had 0.86 and 0.87, respectively. For the FC, LCH consumed more fuel (14.51 L/ha) as compared to MCH (14.25 L/ha). T-test statistical analysis showed that there was no significant difference between LCH and MCH for FE, EFC, FMI and FC. The results suggested that MCH was more efficient and economical in conducting the harvest operation in a rice field.